Rembrandt's beret, or, The painter's crown - Alcorn, Johnny, 1957-; Alcorn, Stephen (New York : Tambourine, 1991)
Tiberius tells how the paintings came alive one day in a museum and Rembrandt painted a picture of Tiberius and gave him his beret and his brushes.
5.5
3-6
3-6
Keywords: Rembrandt Harmenszoon van Rijn, -- 1606-1669 -- Fiction; Painting -- Fiction; Rembrandt Harmenszoon van Rijn -- Fiction; Painting -- Fiction